2019
DOI: 10.1101/520353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting disease-causing variant combinations

Abstract: Notwithstanding important advances in the context of single-variant pathogenicity identification, novel breakthroughs in discerning the origins of many rare diseases require methods able to identify more complex genetic models. We present here the Variant Combinations Pathogenicity Predictor (VarCoPP), a machine-learning approach that identifies pathogenic variant combinations in gene pairs (bi-locus variant combinations). We show that the results produced by this method are highly accurate and precise, an eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The presence of two rare conditions, rather than one disease with phenotypic expansion, is not an unusual finding, particularly, but not exclusively, in consanguineous families. In fact, recent estimates revealed that 7% of the molecularly diagnosed patients carry a combination of two pathogenic variants implicated in distinct Mendelian disorders 10 . Therefore, care should be taken to publish new “broaden” phenotypes in well‐established syndromes particularly those that include “skeletal or muscle changes.” This report also highlights that a precise clinical characterization, and consequently a correct molecular diagnosis, might be hampered by the noncoincident age of onset of each condition, as well as adult‐onset disorders, progressive diseases, and mild phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of two rare conditions, rather than one disease with phenotypic expansion, is not an unusual finding, particularly, but not exclusively, in consanguineous families. In fact, recent estimates revealed that 7% of the molecularly diagnosed patients carry a combination of two pathogenic variants implicated in distinct Mendelian disorders 10 . Therefore, care should be taken to publish new “broaden” phenotypes in well‐established syndromes particularly those that include “skeletal or muscle changes.” This report also highlights that a precise clinical characterization, and consequently a correct molecular diagnosis, might be hampered by the noncoincident age of onset of each condition, as well as adult‐onset disorders, progressive diseases, and mild phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity mapping proved invaluable in identifying variants in recessive Mendelian diseases, particularly in consanguineous families 11,12 . Although rare, phenotypic heterogeneity of typical Mendelian segregating disorders, caused by combined effects in several genes, has been previously described 4,10 . Yet, 44 diseases caused by 213 digenic combinations, involving 136 genes and 364 pathogenic variants, are described at the digenic diseases database (DIDA, https://omictools.com/dida-2-tool, accessed 7 May 2020) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…New machine‐learning methods, like the variant combination pathogenicity predictor (Papadimitriou et al, ), which predicts the pathogenicity of any bilocus variant combination using a variant list from a single individual, might be used to re‐examine data from unsolved PM cases in search of variants in two genes known or suspected to interact. Putative interactions could then be validated in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Digenic inheritance is the simplest form of oligogenic inheritance and refers to disorders resulting from pathogenic variants at two distinct loci (Lupski, ). True digenic inheritance requires the presence of variants at two independent loci to trigger the disease, while composite class inheritance refers to Mendelizing variants with modifiers (Papadimitriou et al, ). Examples of true digenic inheritance in human pathology include facioscapulohumeral muscular dystrophy Type 2 (Lemmers et al, ) or midline craniosynostosis (Timberlake et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation